The harp in contemporary music - Einarsdóttir, Gunnhildur (Sibelius-Akatemia, 2013)
The goal of my doctoral-project is to promote the harp as an important instrument in contemporary music, to show its possibilities, and to encourage composers to write for it in new and inventive ways. My thesis is closely connected with this goal. The thesis, presented in the form of a web site, is a manual of contemporary harp techniques and notation for composers. Although the harp has become increasingly popular in recent years, general knowledge of the instrument's essence, its functions, and in particular its notation still seems to be inadequate and inconsistent. Orchestration books are outdated, and new playing techniques call for new notation guidelines. The web site includes visual and audivisual examples of various harp techniques, both traditional and contemporary. Furthermore notational examples of all techniques are included. The web site is divided into 4 parts. The first part, entitled The harp, includes general information about the harp and its basic functions. Part two, Notation Manual, is a lexicon of conventional and contemporary playing techniques and effects and how to notate them. In this part different aspects of each technique are explained focusing on different parameters; production, sound, notation and range. Part three is a glossary of terms used on the website and additionally includes links to harp-specific websites. The final part consist of a bibliography of books and notation-manuals and a list of reference repertoire played and consulted during the compilation of the web site. My doctoral concerts have focused on demonstrating various aspects of the existing contemporary harp repertoire. From large scale solo harp works to smaller chamber works, the pieces in my concerts have one aspect in common; they are all written by composers who were not harpists themselves. Furthermore, most of the composers have worked closely together with a harpist during the composition of their work. This tradition of harpist-composer co-operation was continued in my work with various composers on numerous new compositions during the doctoral project.
Keywords: notaatio; harppu; nykymusiikki; soittamien; tekniikka; fi=harppu|sv=harpa|en=Harp|